Aim CT Accreditation Program Development for CT X-ray Systems - McTaggart, Douglas (CMBES Proceedings, 2016)
The University Health Network maintains 22 CT X-ray systems at five hospital locations. The problem that was addressed was how to develop and implement a CT Accreditation Program at the University Health Network. This program was developed to satisfy the needs for a standardized annual testing of CT dose and image quality parameters. Appropriate image quality test phantoms were selected and evaluated. This topic deals with the problem of how to develop and implement a CT Accreditation Program for the CT systems at the University Health Network. The project will deal with the selection of image quality and dose phantoms, establishing baseline data derived from the phantoms and storing the data for future reference. Another challenge of the project was to develop a quality assurance program that will satisfy the corporate vision of the University Health Network. This vision is concerned with achieving global impact. The work done in this report will be relevant to Canadian standards and incorporate global standards as well. A comprehensive CT Accreditation Program was then developed and implemented. The program was used to report on CT image quality and dose parameters. It is recommended that the AIM CT Accreditation Program be used at other hospitals to provide comprehensive image quality evaluation, dose monitoring and structured CT reporting.